Persuading consumers with social attitudes - Stefan Buehler; Daniel Halbheer (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper analyzes persuasive advertising and pricing in oligopoly if firms sell differentiated products and consumers have heterogeneous social attitudes towards the consumption by others. Deriving product demand from primitives, we show that the demand-enhancing effect of persuasive advertising varies across consumers and increases in the average degree of conformity. In equilibrium, both quality and cost leaders choose higher advertising intensities and charge higher prices than their competitors. In addition, we show that an increase in the average degree of conformity among consumers reinforces asymmetries between firms.
Keywords: D11; D43; L15; L21; M37; 330; advertising; social attitude; consumption externality; quality; Werbung; Soziale Werte; Konsuminterdependenz; Produktdifferenzierung; Betriebliche Preispolitik; Oligopol; Theorie